2019
DOI: 10.1021/acs.jpcc.9b02324
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Bulk and Surface Properties of Minor Actinide Dioxides MAnO2 (MAn = Np, Am, and Cm); Water Adsorption on Stoichiometric and Reduced {111}, {110}, and {100} Surfaces

Abstract: Hubbard U-corrected generalized gradient approximation density functional theory is used to study the bulk and surface properties of minor actinide dioxides NpO 2 , AmO 2 , and CmO 2 . Comparison of lattice parameters, band gaps, and density of states with experimental data indicates that PBE + U (U = 4.50 eV, J = 0.50 eV) is the best approach of those considered. Stoichiometric and oxygen vacancy defect {111}, {110}, and {100} surfaces are investigated, including the molecular and dissociative adsorptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
8
12
0
Order By: Relevance
“…A similar energy sequence is found for molecular adsorption on Pu 0.92 Am 0.08 O 2 and stoichiometric PuO 2 and AmO 2 surfaces (Figure a), , that is, the stability of molecular adsorption increases from {111} to {100}. Adsorption energies on Pu s of MOX and PuO 2 are similar, as substitution of Am has little influence on surface structure and does not change the charge distribution of Pu s much.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…A similar energy sequence is found for molecular adsorption on Pu 0.92 Am 0.08 O 2 and stoichiometric PuO 2 and AmO 2 surfaces (Figure a), , that is, the stability of molecular adsorption increases from {111} to {100}. Adsorption energies on Pu s of MOX and PuO 2 are similar, as substitution of Am has little influence on surface structure and does not change the charge distribution of Pu s much.…”
Section: Resultssupporting
confidence: 70%
“…O defect generation energies on Pu-Am MOX surfaces with Am on the surfaces are compared with defect generation energies on stoichiometric PuO 2 and AmO 2 surfaces in Figure . , This figure highlights the similar trend in O defect generation energies on stoichiometric AnO 2 and MOX surfaces. On each surface, the O defect generation energy for MOX lies between the corresponding generation energy on PuO 2 and AmO 2 surfaces , and close to their average (1.91, 1.22, and 1.16 eV, respectively, for the {111}, {110}, and {100} surfaces). In our previous work, we found that the O defect generation on AnO 2 surfaces is linearly related with An­(IV)/(III) redox potential.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations